Keep your brain alive : 83 neurobic exercises to help prevent memory loss and increase mental fitness - Katz, Lawrence, 1956-; Rubin, Manning (New York : Workman Publishing Company, 1999)
Offers unusual tasks designed to stimulate brain cell growth.
Keywords: Cognition -- Age factors; Memory -- Age factors; Aging -- Psychological aspects; Cognition -- Problems, exercises, etc